Development of a low-frequency magnetic lightning mapping system (LFM-LMS) in North China: validation and preliminary results - Xiao Li; GaoPeng Lu; FanChao Lyu; HongBo Zhang; Kainat Qamar; RuBin Jiang (Earth and Planetary Physics, 2023)
A low-frequency magnetic lightning mapping system (LFM-LMS) was built during the SHAndong Triggered Lightning Experiment (SHATLE), based on continuous measurements of magnetic field radiation from lightning. The hardware and source-mapping techniques used by the LFM-LMS were introduced; both Monte Carlo simulations and the observation of rocket-triggered lightning examples were employed to examine the location accuracy and detection effectiveness of the LFM-LMS. We estimated that the system’s location accuracy about 100−200 m horizontally and ~200 m vertically. A natural intra-cloud lightning flash and a rocket-triggered lightning flash, both with intricate structures and discharging processes, were examined using the three-dimensional mapping results. The progressing path of negative lightning leaders is usually well-defined, and its propagation speed is estimated to be (0.5−1.4) × 106 m/s. In summary, the LFM-LMS can reconstruct the three-dimensional morphology of lightning flashes; this technology provides a efficient method for investigating the characteristics of lightning development, as well as the overall electrical strucuture of thunderstorms.